2020
DOI: 10.1136/gutjnl-2019-319766
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant gut microbiota alters host metabolome and impacts renal failure in humans and rodents

Abstract: ObjectivePatients with renal failure suffer from symptoms caused by uraemic toxins, possibly of gut microbial origin, as deduced from studies in animals. The aim of the study is to characterise relationships between the intestinal microbiome composition, uraemic toxins and renal failure symptoms in human end-stage renal disease (ESRD).DesignCharacterisation of gut microbiome, serum and faecal metabolome and human phenotypes in a cohort of 223 patients with ESRD and 69 healthy controls. Multidimensional data in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
304
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 322 publications
(351 citation statements)
references
References 53 publications
12
304
0
1
Order By: Relevance
“…Permutational multivariate analysis of variance (PERMANOVA) was performed with the adonis function of the vegan package, and the adonis P-value was generated based on 1,000 permutations. The method of effect size analysis was referred as Wang et al [10]. The no-metric multidimensional scaling (NMDS) analysis was used as the ordination methods (metaMDS function in vegan package) for compositional data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Permutational multivariate analysis of variance (PERMANOVA) was performed with the adonis function of the vegan package, and the adonis P-value was generated based on 1,000 permutations. The method of effect size analysis was referred as Wang et al [10]. The no-metric multidimensional scaling (NMDS) analysis was used as the ordination methods (metaMDS function in vegan package) for compositional data.…”
Section: Resultsmentioning
confidence: 99%
“…amplicon or whole-metagenomic sequencing), the gut bacterial community have been well studied over the past years [6][7][8]. Gut bacteria was shown to exert profound effects on regulating host metabolism [9,10], and thereby had been linked to host health and diseases [11,12]. However, as another part of the gut microbial ecosystem, the holistic viral community of enteric microbiome (or "gut virome") was less well characterized [13].…”
Section: Introductionmentioning
confidence: 99%
“…and Lactobacillus spp., and an elevation of Enterobacteriaceae and Escherichia coli with progressive stages of CKD [20]. Recently, Wang et al demonstrated that alterations in the gut microbiome mediate metabolome changes in patients with ESKD [21]. The alterations in the gut microbial composition, as a potential cause of a change in the gut biochemical milieu in CKD, is further enhanced by several uremia-related factors, while the gut microbiota per se also contribute to CKD by generating the uremic toxin precursor metabolites.…”
Section: Gut Dysbiosis In Ckdmentioning
confidence: 99%
“…Therefore, the discovery of a new treatment to delay CRF progression would be an important step toward achieving improved general kidney health. There are many factors that contribute to CRF progression, including increased production of oxidative stress and acidosis, proinflammatory cytokines, chronic and recurrent infections, altered metabolism of adipose tissue, and last but not least gut microbiota dysbiosis, which is a source of systematic microinflammation in vivo (Machowska et al, 2016;Mahmoodpoor et al, 2017;Wang et al, 2020). Currently, investigators concern that gut microbiota dysbiosis and microinflammatory lesions play fundamental roles during CRF progression.…”
Section: Introductionmentioning
confidence: 99%